Formation of Nanoscale Bioimprints of Muscle Cells Using UV-Cured Spin-Coated Polymers - Fahmi Samsuri; John S. Mitchell; Maan M. Alkaisi; John J. Evans (Journal of Nanotechnology)
We report a nanoscale replication method suitable for biological specimens that has potential in single cell studies and in formation of 3D biocompatible scaffolds. Earlier studies using a heat-curable polydimethylsiloxane (PDMS) or a UV-curable elastomer introduced Bioimprint replication to facilitate cell imaging. However, the replicating conditions for thermal polymerization are known to cause cell dehydration during curing. In this study, a UV-cured methacrylate copolymer was developed for use in creating replicas of living cells and was tested on rat muscle cells. Bioimprints of muscle cells were formed by spin coating under UV irradiation. The polymer replicas were then separated from the muscle cells and were analyzed under an Atomic Force Microscope (AFM), in tapping mode, because it has low tip-sample forces and thus will not destroy the fine structures of the imprint. The new polymer is biocompatible with higher replication resolution and has a faster curing process than other types of silicon-based organic polymers such as PDMS. High resolution images of the muscle cell imprints showed the micro-and nanostructures of the muscle cells, including cellular fibers and structures within the cell membranes. The AFM is able to image features at nanoscale resolution with the potential for recognizing abnormalities on cell membranes at early stages of disease progression.